2017
DOI: 10.1589/jpts.29.144
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of massage and electrotherapy on muscle tone, stiffness and muscle contraction following gastrocnemius muscle fatigue

Abstract: [Purpose] This study aimed to examine the effects of a combined intervention consisting of massage therapy and transcutaneous electrical nerve stimulation on gastrocnemius muscle fatigue, assessing whether the intervention improved muscle tone, stiffness, and muscle contraction. [Subjects and Methods] The subjects were 20 healthy males in their 20s who were equally divided into a transcutaneous electrical nerve stimulation group and a combined therapy group that received a combination of massage therapy and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The present study has shown that the stiffness of the 3 levels of AT and PF performed with the knee flexed was significantly smaller than when the knee was fully extended (Figures 2, 3, respectively). Le Sant et al suggested that the passive torque with the knee flexed 90° was smaller, indicating a smaller total stiffness in the lower leg muscles [10]. The present study indicates that MG and LG are under very little tension with the knee flexed 90° (Figure 1).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The present study has shown that the stiffness of the 3 levels of AT and PF performed with the knee flexed was significantly smaller than when the knee was fully extended (Figures 2, 3, respectively). Le Sant et al suggested that the passive torque with the knee flexed 90° was smaller, indicating a smaller total stiffness in the lower leg muscles [10]. The present study indicates that MG and LG are under very little tension with the knee flexed 90° (Figure 1).…”
Section: Discussionsupporting
confidence: 51%
“…Compared with the single-axis accelerometer in the Myoton-2 and Myoton-3 devices, the MyotonPRO device has a tri-axial accelerometer, making it more versatile in terms of application [7]. Investigators in various fields have used the device, including in sport medicine [8,9], rehabilitation [10], and spaceflight [11]. Previous studies have shown that the MyotonPRO can reliably assess stiffness of MG, the lateral head of the gastrocnemius (LG), AT, and plantar fascia (PF) [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Masticatory muscles are clenched and chewing with neuromuscular control of the trigeminal nerve, but masticatory muscle fibers are type II muscle fibers predominate (temporal muscle: 52% to 73%, masseter muscle: 48% to 65%), this muscle activity decreases due to rapid muscle fatigue ( Mao et al, 1992 ). Conversely, in healthy adults, continuous muscular contraction of specific muscles immediately increased muscle tone and stiffness significantly ( Wang, 2017 ). Therefore, the changes in muscle activity and stiffness of connective tissue after training may have opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommended wearing a mouthguard in taekwondo athletes and performing a massage or a stretching on the masticatory muscles to reduce increased stiffness in the nondominant or dominant side after weight training. Actually, the rehabilitation program combined with massage and transcutaneous electrical nerve stimulation is effective in reducing muscle tone and stiffness caused by continuous strong muscle contraction ( Nakamura et al, 2018 ; Wang, 2017 ). Moreover, the high-intensity weight training for taekwondo athletes is very important for their successful competition.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the muscle torque and exhibits an analgesic effect by increasing the pain threshold [6]. The second technique is massage, which is applied to soft tissues and can contribute to alteration of blood flow, blood pressure, and skin temperature using the hands, a vibrator, and a roller [7,8]. The third technique is MET followed by relaxation and passive stretching (PS).…”
Section: Introductionmentioning
confidence: 99%